Toward recovery-oriented perinatal healthcare: A participatory qualitative exploration of persons with lived experience and health providers’ views and experiences - Marine Dubreucq; Mathilde Thiollier; Sarah Tebeka; Pierre Fourneret; Marion Leboyer; Sylvie Viaux-Savelon; Catherine Massoubre; Corinne Dupont; Julien Dubreucq (European Psychiatry, 2023)
Abstract